Parent Education Model for Children (Study of the Story of the Prophet Zakariya towards Siti Maryam in Surah Al-Imran Verse 37) - Didik Himmawan; Saskia Ambareksa (Konsultan Jurnal Ilmiah Indonesia, 2025)
Education can be carried out anywhere, whether in the family environment, school environment or in the community environment. As a parent, you are obliged to provide education to your child in relation to your child's education as the main educator. Therefore, parents' responsibilities regarding children's education include providing encouragement or motivation, whether it is love, responsibility for the child's welfare, both physically and mentally. The educational goals to be achieved include cognitive concepts, affective and spiritual aspects to create a balanced personality based on the idea that the implementation of education has not fully achieved its goals, especially in Islamic education. And the method used in this research is the analysis of Surah Al-Imran verse 37. The aim of this research is to find out the Model of Parental Education for Children (Study of the Story Prophet Zakariya towards Siti Maryam in Surah Al-Imran Verse 37). The results of this research show that a good environment for children starts from the smallest and closest environment, namely the family. If parents want pious and pious children, then create a family environment that is sakinah, mawaddah, warahmah.